Environmental Health Impacts and Risks of Domestic Wastewater Issues in Small Island - Iga Maliga; Suryo Purwono; Rika Harini; Herni Hasifah; Ana Lestari (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
The problem of domestic wastewater on small islands poses a significant threat to the surrounding marine ecosystem. Generally, residents of small islands tend to overlook the sanitation aspects of domestic wastewater. The contents of domestic wastewater can harm environmental ecosystems and act as vectors for diseases within the community. This study aims to assess the sanitation risk index of domestic wastewater and its impact on environmental and public health. The research was conducted on Bungin Island in May 2024, using a mixed-methods approach with a Sequential Explanatory Design. The study involved 274 households as respondents and six key informants. Research instruments included questionnaires, observation sheets, and interview guides. Data collected were analyzed using Microsoft Excel 2013 and IBM SPSS version 29.0, while interview and observation data were processed using NVIVO version 14.0. The findings indicate that residents generally do not perceive domestic wastewater as a potential problem. Bungin Island falls into the high-risk category for sanitation, impacting fish ecosystems, coral reefs, and contributing to marine pollution. Furthermore, it acts as a driving factor for diarrheal diseases and stunting in children. In conclusion, poor sanitation conditions have direct and indirect impacts on environmental ecosystems and public health. Integrated efforts are thus essential to address domestic wastewater issues on densely populated small islands.